Post 9/11 War on Terror: A Study of Dynamics of Neocolonialism in Aslam’s Thinner Than Skin - Hafeez, Saima; Rasool, Shamshad; Anwar, Behzad (Annals of Human and Social Sciences, 2024)
The concept of Neo-Colonialism is perhaps the most relevant issue in the present-day scenario in Third World countries. This research aims at analysing Aslam’s Thinner than Skin in the context of post 9/11 War on Terror and American hegemony strengthening political, cultural and economic control of Pakistan. A conceptual framework has been employed to undertake this research with special emphasis on Nkrumah’s concept of Neo-Colonialism along with supporting concepts of Said and Spivak. This study is qualitative in nature and the Textual Analysis has been employed to analyse the neo-colonial designs of the USA with special repercussions of the War on Terror in this specific region. The results show that the different forms of American neo-colonialism including political, cultural and economic are used to have an indirect control of the country. This study recommends that the contemporary power politics should be perceived from the perspective of Neo-Colonialism to have a true implication.